2022
DOI: 10.1088/1742-5468/ac52a4
|View full text |Cite
|
Sign up to set email alerts
|

Statistical aspects of interface adhesion and detachment of hierarchically patterned structures

Abstract: We introduce a three dimensional model for interface failure of hierarchical materials adhering to heterogeneous substrates. We find that the hierarchical structure induces scale invariant detachment patterns, which in the limit of low interface disorder prevent interface failure by crack propagation (‘detachment fronts’). In the opposite limit of high interface disorder, hierarchical patterns ensure enhanced work of failure as compared to reference non-hierarchical structures. While the study of hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Failure of network links occurs once the corresponding current exceeds a threshold value 32 , 33 . Our motivation to use the RFN is that this model not only is endowed with an evident network structure but has also been extensively studied for representation of basic features of failure processes in disordered materials 34 , including materials with hierarchical microstructures 11 , 12 . In the simulations, we follow the standard quasi-static deformation protocol 34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure of network links occurs once the corresponding current exceeds a threshold value 32 , 33 . Our motivation to use the RFN is that this model not only is endowed with an evident network structure but has also been extensively studied for representation of basic features of failure processes in disordered materials 34 , including materials with hierarchical microstructures 11 , 12 . In the simulations, we follow the standard quasi-static deformation protocol 34 .…”
Section: Methodsmentioning
confidence: 99%
“…The peak stress signals an important deformation stage notably in non hierarchical RFN structures, where it separates a regime of stable, statistically homogeneous damage accumulation from a failure regime which is dominated by damage localization leading to nucleation and growth of a critical crack 34 . In HFN structures, instead, a system that has reached and passed peak stress still exhibits damage accumulation and prevents the formation of critical cracks, a fact that may result in an extended post-peak regime 11 , 12 .…”
Section: Methodsmentioning
confidence: 99%
“…The failure behavior of hierarchical materials, as well as the resulting super-rough crack morphology, was found to differ significantly from the behavior of nonhierarchical ones. Hierarchical patterning of interfaces was also studied using fuse network models, and it was shown that hierarchical patterning delays detachment and improves interfacial adhesion [11]. Hosseini et al [12] introduced a hierarchical version of a beam network model to simulate hierarchically patterned materials.…”
Section: Introductionmentioning
confidence: 99%